Working in policing - Pepper, Ian K. (Policing matters, 2011)
Aimed at new recruits or HE students thinking about a career in policing, this book provides a clear overview of and insight into the many and varied roles available. From a neighbourhood police officer or a detective, to a crime scene investigator gathering evidence or an analyst collating intelligence, the book examines what each role entails, the skills required, and the best pathway to securing the job. An extended case study runs through the book, demonstrating how the different roles are involved in and contribute to a single investigation, and self-assessment questions relating to each role check the reader's understanding.